Extraction, Chemical Functionalization, and Application of Stipa obtusa Cellulose Microfibers for Lead Ion Adsorption - Willis Villar, Luhana Guadalupe (2025)
Environmental contamination by heavy metals, such as lead (Pb2+), presents significant risks to ecosystems and public health, necessitating the development of innovative and sustainable remediation methods. This study introduces a novel adsorbent derived from microcellulose (MC) extracted from Stipa obtusa, a grass species native to the Andean regions of Peru, Ecuador, and Bolivia, for the removal of lead ions from aqueous solutions. MC fibers were isolated through thermochemical processing, followed by chemical functionalization with sodium chlorite (NaClO2). The resulting functionalized microfibers (FMC) were characterized using elemental analysis, Fourier-transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller surface area analysis (BET), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). Batch adsorption experiments identified optimal conditions: an adsorbent dosage of 0.4 mg/L, pH 5, and a contact time of 60 min, achieving a maximum adsorption capacity of 34 mg/g. Kinetic studies indicated the adsorption process followed a pseudo-second-order model, while the adsorption isotherm data best fitted the Freundlich model, indicating a heterogeneous adsorption process. These results demonstrate the potential of FMC as an efficient and environmentally friendly adsorbent for heavy metal ion removal in water treatment.